Comparison of transient elastography (FibroScan), FibroTest, APRI and two algorithms combining these non‐invasive tests for liver fibrosis staging in HIV/HCV coinfected patients: ANRS CO13 HEPAVIH and FIBROSTIC collaboration. Issue 1 (6th September 2013) - Castera, L; Winnock, M; Pambrun, E; Paradis, V; Perez, P; Loko, M‐A; Asselineau, J; Dabis, F; Degos, F; Salmon, D
<x xml:space="preserve">Abstract</x> Objectives Combining noninvasive tests increases diagnostic accuracy for staging liver fibrosis in hepatitis C virus (HCV)‐infected patients, but this strategy remains to be validated in HIV/HCV coinfection. We compared the performances of transient elastography (TE), Fibrotest (FT), the aspartate aminotransferase‐to‐platelet ratio index (APRI) and two algorithms combining TE and FT (Castera) or APRI and FT (SAFE) in HIV/HCV coinfection. Methods One hundred and sixteen HIV/HCV‐coinfected patients (64% male; median age 44 years) enrolled in two French multicentre studies (the HEPAVIH cohort and FIBROSTIC) for whom TE, FT and APRI data were available were included in the study. Diagnostic accuracies for significant fibrosis (METAVIR F ≥ 2) and cirrhosis (F4) were evaluated by measuring the area under the receiver‐operating characteristic curve (AUROC) and calculating percentages of correctly classified (CC) patients, taking liver biopsy as a reference. Results For F ≥ 2, both TE and FT (AUROC = 0.87 and 0.85, respectively) had a better diagnostic performance than APRI (AUROC = 0.71; P < 0.005). Although the percentage of CC patients was significantly higher with Castera's algorithm than with SAFE (61.2% vs. 31.9%, respectively; P < 0.0001), this percentage was lower than that for TE (80.2%; P < 0.0001) or FT (73.3%; P < 0.0001) taken separately. For F4, TE (AUROC = 0.92) had a better performance than FT (AUROC = 0.78; P = 0.005) or APRI (AUROC = 0.73; P = 0.025). Although the percentage of CC patients was significantly higher with the SAFE algorithm than with Castera's (76.7% vs. 68.1%, respectively; P < 0.050), it was still lower than that for TE (85.3%; P < 0.033). Conclusions In HIV/HCV‐coinfected patients, TE and FT have a similar diagnostic accuracy for significant fibrosis, whereas for cirrhosis TE has the best accuracy. The use of the SAFE and Castera algorithms does not seem to improve diagnostic performance.